Mechanical Behavior of Clay Soil Stabilized with Fly Ash and Bottom Ash - Nugroho, Soewignjo Agus; Zulnasari, Azra; Fatnanta, Ferry; Putra, Andius Dasa (Makara Journal of Technology, 2022)
Soil is one of the most important aspects of an infrastructure given its functions of receiving and holding structural loads. However, not all soils have good physical and mechanical properties. To overcome those conditions, stabilization of the soil is practiced to meet the technical requirements. This study aims to determine the behavior of high plasticity clay stabilized with lime, fly ash, and bottom ash. These additives can be used as a stabilizing agent to increase soil strength. The percentage of additives varied from 5%–25% then mixed with clay and were tested through the (Unconfined Compression Strength (UCS) test. The UCS test was carried out with 6 treatments, including consecutively non-curing and unsoaked, non-curing and soaked, curing for 7 days and unsoaked, cured for 7 days and soaked, cured for 28 days and unsoaked, and cured for 28 days and soaked. Results show that the UCS value increased along with the span of curing time. Meanwhile, the soaking treatment of the sample decreased the UCS value.